PEMBERDAYAAN KOMUNITAS OLAHRAGA DESA BALUK - NEGARA MELALUI PELATIHAN WASIT TENIS MEJA BERBASIS PARTISIPATIF - Agus Adi Saputra I Gede; Diah Asrida Putu (Fakultas Teknik dan Informatika Universitas PGRI Mahadewa Indonesia, 2025)
This community service program aimed to empower the sports community of Baluk Village – Negara through a table tennis umpire training designed to support the organization of professional and sustainable local tournaments. The activity applied a participatory direct training approach, consisting of three main stages: (1) preparation, involving coordination with village officials and local sports organizations; (2) implementation, including theoretical sessions and match simulations; and (3) evaluation and mentoring through direct observation of participants’ performance. The program was attended by 25 participants, comprising youth organization members, physical education teachers, and village officials. The evaluation results indicated a significant improvement in participants’ competencies, with technical aspects averaging 80% (good), non-technical aspects 89% (very good), and full attendance and participation (100%). Beyond technical mastery, the activity strengthened sportsmanship values, cooperation, and social cohesion within the village sports community. In conclusion, this participatory training method proved effective in enhancing the capacity of local human resources in sports, fostering community collaboration, and promoting independence in organizing village-level sports events. This program serves as a replicable model for community empowerment through sports education, encouraging continuous collaboration between universities, village governments, and local communities